Conflict Management and Performance of Health Care Professionals in Teaching Hospitals in Rivers State - Adim, Chidiebere; Odili, Chukwuemeka; Aigboje, Patrick (European Journal of Human Resource, 2020)
Purpose: The purpose of this study is to conflict management and performance of health care professionals in Teaching Hospitals in Rivers State. Methodology: The study used a cross sectional research design involving medical doctors, nurses, medical laboratory scientists and pharmacists in University of Port Harcourt Teaching Hospital and Rivers State University Teaching Hospital. A Multi-stage sampling was employed to select 165 healthcare professionals from both hospitals. The reliability of the instrument was achieved by the use of the Cronbach Alpha coefficient with all the items scoring above 0.70. The hypotheses were tested using the Spearman's Rank Order Correlation Coefficient with the aid of Statistical Package for Social Sciences version 23.0. The tests were carried out at a 95% confidence interval and a 0.05 level of significance. Findings: Results from analysis of data revealed that conflict management significantly predict performance of health care professionals in Teaching Hospitals in Rivers State. Recommendation: The study recommends that health care professionals' collaboration should be adopted in Teaching Hospitals. This includes sharing of patient information, joint participation in the care and in the decision-making process, and degree of cooperation, must be carefully scrutinized and implemented with the added input of nurses, physicians and other paramedics.